Antihyperglycemic effect of carvone: Effect on the levels of glycoprotein components in streptozotocin-induced diabetic rats - Udaiyar Muruganathan; Subramani Srinivasan; Dhananjayan Indumathi (Journal of Acute Disease, 2013)
Objective: To investigate the effect of carvone on dearrangement in glycoprotein levels in the streptozotocin(STZ)-induced diabetic model. Methods: Diabetes was induced in male Wistar rats by a single intraperitoneal injection of STZ (40 mg/kg b.w). The levels of glycoproteins were altered in experimental diabetes mellitus. Carvone were administered to diabetic rats intragastrically at 25, 50, 100 mg/kg bw for 30 d. The effects of carvone on plasma glucose, insulin, plasma and tissue glycoproteins were studied. Results: Oral administration of carvone (50 mg/kg b.w) for 30 d, dose dependently improved the glycemic status in STZ-induced diabetic rats. The levels of plasma glucose were decreased with significant increase of plasma insulin level. The altered levels of plasma and tissue glycoprotein components were restored to near normal. Conclusions: The present findings suggest that carvone can potentially ameliorate glycoprotein components abnormalities in addition to its antihyperglycemic effect in experimental diabetes. In light of these advantageous results, it is advisable to broaden the scale of use of carvone in a trial to alleviate the adverse effects of diabetes.